PEMANFAATAN TIMBANGAN DARI LIMBAH KAYU DAN BUKU POP-UP SEBAGAI UPAYA PENGEMBANGAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DI SLB TUNAGRAHITA GUGUS KELOMPOK KERJA GURU (KKG) KABUPATEN CIREBON - Dina Pratiwi Dwi Santi; Herri Sulaiman; Maya Dewi Kurnia (Al-Khidmat, 2019)
Mental retardation is a child who has below average intelligence. In other words, they have less learning ability compared to others. This situation caused them difficulty in understanding abstract mathematical material. In addition, it appears that the material presented by the teacher is considered to be less interesting and boring by them. Though the model of the presentation of material that is fun, interesting, and easy to understand is one of the factors that influence their learning success. They are bored with the model of presenting the material using the media that the teacher uses repeatedly. Therefore, teachers' creativity and innovation are needed in utilizing the media and being able to package it into concepts that are interesting and fun for their students. So that the learning needs can be met optimally. Thus, this service aims to improve teacher skills in utilizing instructional media in the form of wooden scales and pop-up. Thus, through community service activities, it is expected to be able to provide benefits to teachers of mentally retarded KKG groups in Cirebon District, namely: (a) increase teacher knowledge about mathematics learning by utilizing learning media (b) enhancing teacher pedagogical competence by utilizing scales from wood waste and pop-up books. up to teach retarded students.